Comparison of Vestibular Function Between Right and Left Handed Normal Population - Bhandari, Sharma; Shrestha, Sagun; Saxena, R.K. (Journal of Nepalgunj Medical College, 2018)
Objective To identify the side of vestibular dominance in right handed & left handed people. Method A total of 50 normal subjects, aged between 15 - 45 years were included as Left handers (n = 25) and Right handers (n = 25). Handedness was confirmed by the Annett Hand Preference Questionnaire. Bithermal caloric testing was done which was recorded by Electronystagmography (ENG). Maximum Slow Phase Velocity (MSPV) was taken as the parameter of choice. Directional Preponderance (DP) and Canal Paresis (CP) were calculated in each group. Results Out of the 25 Left handed subjects, 8 had DP towards Left whereas 7 had DP towards the Right and the remaining 10 showed no DP to any side (normal) (p<0.001). Out of the 25 Right handed subjects, 4 had DP towards Right and none had DP towards the Left, remaining 21 showed no DP to any side (normal) (p<0.001). For CP, out of 25 Left handed subjects, 2 showed CP towards the Left and 1 towards the Right, the remaining 22 showed no CP (normal) at all. Similarly out of the 25 Right handed subjects, 2 showed CP towards the Left and 1 towards the Right, the remaining 22 showed no CP (normal) at all. Out of 25 Right handers, it was found that Right handers showed Right vestibular preference whereas vestibular preference was almost equally distributed to Left and Right side in Left handers. Conclusion On considering DP, it was found that Right handers showed Right vestibular preference whereas vestibular preference was almost equally distributed toLeft and Right side in Left handers (p<0.001).